2020
DOI: 10.2147/cmar.s277013
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Significance of Platelet–Albumin–Bilirubin (PALBI) Grade in Hepatocellular Carcinoma Patients Stratified According to Platelet Count</p>

Abstract: Background Platelet–albumin–bilirubin (PALBI) has been demonstrated to be superior to conventional Child–Pugh (C-P) grade in evaluating liver function and prognosis of HCC patients. However, both thrombocytosis and thrombocytopenia are unfavorable for HCC survival. The aim of this study was to preliminarily investigate the prognostic value of PALBI in HCC patients with thrombocytopenia and excluding thrombocytopenia. Methods In this retrospective cohort study, we review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
0
13
1
1
Order By: Relevance
“…However, our AUC with MELD‐Na (AUC = 0.63 and 0.64 for severe PHLF and 30‐day mortality, respectively) was greater than the values reported by Fagenson et al (AUC = 0.6 and 0.58 for severe PHLF and 30‐day mortality, respectively) potentially because we used the updated MELD‐Na formula 23 as opposed to the traditional MELD formula 14 . Hypoalbuminemia and hyperbilirubinemia are highly important objective surrogates for poor nutritional status, severe liver injury, and high risk of recurrence 20,32 . While the MELD‐Na score includes preoperative bilirubin level, the CTP scoring system includes both preoperative albumin and bilirubin level.…”
Section: Discussioncontrasting
confidence: 60%
See 4 more Smart Citations
“…However, our AUC with MELD‐Na (AUC = 0.63 and 0.64 for severe PHLF and 30‐day mortality, respectively) was greater than the values reported by Fagenson et al (AUC = 0.6 and 0.58 for severe PHLF and 30‐day mortality, respectively) potentially because we used the updated MELD‐Na formula 23 as opposed to the traditional MELD formula 14 . Hypoalbuminemia and hyperbilirubinemia are highly important objective surrogates for poor nutritional status, severe liver injury, and high risk of recurrence 20,32 . While the MELD‐Na score includes preoperative bilirubin level, the CTP scoring system includes both preoperative albumin and bilirubin level.…”
Section: Discussioncontrasting
confidence: 60%
“…This study also showed no association between higher PALBI grades and development of severe PHLF, consistent with Xu et al 19 and Ye et al 16 PALBI had no statistical difference in predictive accuracy compared to MELD‐Na. Besides having a statistically robust equation, the proposed theory of better predictive power with PALBI comes from including blood platelet count, an indicator for the severity of preoperative portal hypertension, which is associated with higher rates of complications and survival after hepatic resection 18,20,28 . A lower platelet level is associated with worse portal hypertension 28 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations